Hybrid Cloud Architectures for Scalable and Cost-Effective AI in Banking - Vedaswaroop Meduri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The banking sector's digital transformation through hybrid cloud architectures represents a strategic response to the growing demands for scalable, secure, and cost-effective AI implementations. This article examines the comprehensive integration of hybrid cloud solutions in banking, exploring key components, implementation strategies, and security considerations. The article covers infrastructure requirements, data management frameworks, deployment methodologies, and financial implications of hybrid cloud adoption. Special attention is given to regulatory compliance, data protection measures, and emerging technologies such as edge computing and advanced AI capabilities. The article demonstrates how hybrid cloud architectures enable banks to maintain security and compliance while leveraging the benefits of cloud-based AI/ML capabilities, ultimately driving innovation and operational efficiency in the financial services sector.
Keywords: Banking Digital Transformation; Hybrid Cloud Banking; AI Financial Infrastructure; Cloud Security Compliance; Edge Computing Integration